State of the Russian pharmaceutical industry at the present stage - E. N. Hoseva (Izdatelstvo OKI, 2018)
Review article presents the features of the state of the Russian pharmaceutical industry at the present stage, the main problems and difficulties of the transition of Russian pharmaceutical manufacturers to the standards of GMP, the state program of development of the industry.